2019
DOI: 10.1021/acsomega.8b03309
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Mn3O4Nanowalls Grown on Carbon Fibers as Electrodes for Flexible Supercapacitors

Abstract: Emerging flexible and wearable electronic devices necessitates the development of fiber-type energy storage devices to power them. Supercapacitors received great attention for applications in flexible and wearable devices due to their scalability, safety, and miniature size. Herein, we report the fabrication of a flexible supercapacitor using manganese(II,III) oxide (Mn 3 O 4 ) nanowalls (NWs) grown by electrochemical deposition on carbon fiber (CF) as electrode-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 70 publications
1
18
0
Order By: Relevance
“…The use of Mn 3 O 4 NWs grown on CF as an electrode in a symmetric supercapacitor is reported previously. 42 The scanning electron microscopy (SEM) image of Mn 3 O 4 NWs grown on CF is shown in Figure 7 a from which it can be observed that the Mn 3 O 4 NWs are grown on CF uniformly with a porous architecture. In order to understand the electrochemical performance of the Mn 3 O 4 NWs, the CV study is conducted within a potential window of 0–0.8 V in a 3.5 M KOH aqueous electrolyte.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of Mn 3 O 4 NWs grown on CF as an electrode in a symmetric supercapacitor is reported previously. 42 The scanning electron microscopy (SEM) image of Mn 3 O 4 NWs grown on CF is shown in Figure 7 a from which it can be observed that the Mn 3 O 4 NWs are grown on CF uniformly with a porous architecture. In order to understand the electrochemical performance of the Mn 3 O 4 NWs, the CV study is conducted within a potential window of 0–0.8 V in a 3.5 M KOH aqueous electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…The electrochemical deposition method was used in the synthesis of two-dimensional Mn 3 O 4 NWs on the CF substrate as per the literature. 42 In a typical procedure, an electrochemical deposition bath consisting of 0.16 M Na 2 SO 4 and 0.16 M manganese acetate tetrahydrate was used in a three-electrode cell in which a surface-pretreated CF substrate was used as the working electrode, Ag/AgCl was used as the reference electrode, and platinum foil was used as the counter electrode. Mn 3 O 4 NWs were deposited at a constant potential of −1.8 V for a period of 20 min through the chronoamperometry technique.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific capacitance retention of Mn 3 O 4 electrodes increases gradually and reaches a highest value, and thereafter slowly decreases, the phenomenon may be attributed to the following reasons. First, electrolyte ions gradually penetrate into the interior of electrode materials and open more pore of electrode materials at the beginning stage of charge-discharge cycles, which will enhance the faradic reactions [47]. Second, the electrode is gradually wetted, which will increase the active sites of electrode materials and promote the faraday reaction [48,49].…”
Section: Resultsmentioning
confidence: 99%
“…As is well known, manganese oxides are frequently used as, for instance, electrode materials for chemical current sources, 13 electrochemical sensors, 4 adsorbents, 57 etc. These oxides are also considered as promising noble metal-free electrocatalysts for the decomposition of water by electrolysis.…”
Section: Introductionmentioning
confidence: 99%